The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1159/000329931
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections and Sexual Practices among Injecting Drug Users in Harm Reduction Centers in Catalonia

Abstract: Background: The objectives of the study were to estimate the prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae and sexual risk practices, and to identify factors associated with infection by C. trachomatis/N. gonorrhoeae. Methods: Injecting drug users were interviewed at harm reduction centers and biological samples were collected to estimate the prevalence of C. trachomatis and N. gonorrhoeae. Results: The prevalence of C. trachomatis was 2.3%, and this was higher among immigrants (3.6%); the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…In order to reverse this trend, the Spanish National AIDS Plan recommends promoting condom use, HIV testing, rapid access to Antiretroviral Therapy (ART), and Post-exposure Prophylaxis (PEP) [ 2 ]. However, it has been strongly demonstrated that condoms are not used consistently among some groups of MSM who are at high risk of being infected with HIV [ 3 , 4 ]. Overall, undiagnosed HIV is estimated to be between 14% and 22% of people living with HIV [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to reverse this trend, the Spanish National AIDS Plan recommends promoting condom use, HIV testing, rapid access to Antiretroviral Therapy (ART), and Post-exposure Prophylaxis (PEP) [ 2 ]. However, it has been strongly demonstrated that condoms are not used consistently among some groups of MSM who are at high risk of being infected with HIV [ 3 , 4 ]. Overall, undiagnosed HIV is estimated to be between 14% and 22% of people living with HIV [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sharing injection equipment may be something that the latter expect to do and so they could thus be more likely to take protective measures and develop a habit of cleaning used needles and syringes. Injection frequency has also been found to be associated with HCV in a number of social and cultural contexts [20,21,22]. Constrained financial resources due to frequent drug consumption increase the need to share drugs and injection paraphernalia.…”
Section: Discussionmentioning
confidence: 99%
“…Further details on this collaborative project are presented elsewhere [19,20]. Methods of the included studies are described in detail elsewhere [21][22][23][24][25][26][27]; therefore, only a summary is presented here (Appendix 1, http://links. lww.com/QAD/A520).…”
Section: Methodsmentioning
confidence: 99%